Cyclometalated Ni(II) Complexes [Ni((NCN)-C-boolean AND-N-boolean AND)X] of the Tridentate 2,6-di(2-pyridyl)phen-ide Ligand - Kletsch, Lukas; Hoerner, Gerald; Klein, Axel (Organometallics, 2020)
A series of cyclometalated Ni(II) complexes [Ni(PyPhPy)X] containing anionic (NCN-)-C-boolean AND-N-boolean AND tridentate ligand Py(Ph-)Py 2,6-di(2-pyridyl)benzene1-ide, (Py(HPh)Py = 1,3-di(2-pyridyl)benzene) and X = Cl, Br, or I as coligands, were studied. All three complexes were obtained through direct C-H base-assisted nickelation from NiX2 and Py(HPh)Py using KOAc/K2CO3 in nonpolar high-boiling point solvents. While the overall molecular structures are quite similar to those of the previously studied [Ni((CNN)-N-boolean AND-N-boolean AND)X] complexes with the anionic (CNN)-N-boolean AND-N-boolean AND tridentate -Phbpy (HPhbpy = 6-(phenyl)-2,2'-bipyridine) ligand, bond lengths in the molecular structures are slightly different. Large differences between these (NCN)-C-boolean AND-N-boolean AND and (CNN)-N-boolean AND-N-boolean AND Ni complexes which can be traced to the different orientation of the X coligand to the carbanionic phen-ide group, trans or cis, and the different ligand pattern, Py-Ph-Py versus Ph-Py-Py, were found for the UV-vis absorption spectra and the electrochemical reductions, while the oxidation potentials are very similar. Extended DFT calculations with the TPSSh functional associate the indifference of oxidation potentials with conserved energies of metal-borne HOMOs. By contrast, the diminished pi-acceptor qualities of the (NCN)-C-boolean AND-N-boolean AND ligand translate into a destabilization of the LUMO by ca. 400 mV and a blue-shift of the leading visible transition by 80 nm in very good agreement with the experimental data.